The Influence of Corporate Governance and Competitive Advantage on Firm Value - Suroto, Suroto; Nuzula, Nila Firdausi; Worokinasih, Saparila (FIA UB, 2025)
This study analyzes previous research to understand the influence of corporate governance and competitive advantage on firm value. The research employs a literature review method, gathering and analyzing data from existing written sources such as scientific journals, e-books, theses, books, and magazines to comprehensively understand the discussed topic. This study integrates various theories, including agency theory, resource-based view theory (RBV), and market orientation theory, to explain the relationships between variables. As a literature review article, this study contributes to deepening the understanding of the impact of corporate governance, competitive advantage, and firm value. The practical implications of this literature review emphasize the need to strengthen effective corporate governance practices and develop competitive advantage as strategies to enhance firm value. Furthermore, this article has implications for management, investors, regulators, and future research, given the scarcity of prior studies that utilize this theoretical framework to examine similar research models.